(untitled) (Estudios humanísticos. Geografía, historia y arte, 1997)
The constitutional Spanish tradition has, in their beginnings, common aspects with the modern revolutions: English, American and French. The Spanish philosophers and, also, the politicians received the influence of the European philosophers and English. Alvaro Flórez Estrada knew the thought of the most important thinkers of the XVIII Century and beginnings of the XIX Century, it is possible to highlight the special influence of Rousseau, that showed, mainly, in the project of constitution which is written in 1809, in orden to discuss in the Courts (Parlament) of Cádiz, as this work seeks to show.